North elevation of Shiva Temple 1 - Temples of India Project Team (Jio Institute, 2024)
In the north elevation of the garbhagriha (sanctum sanctorum) of Shiva Temple 1, all the niches are empty at present. The shikhara (superstructure) of the temple has collapsed with time and only remnants of stone blocks can be seen.